PENERAPAN STRATEGI PREVIEW QUESTION READ REFLECT RECITE REVIEW (PQ4R) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN WACANA SISWA KELAS IV SEKOLAH DASAR NEGERI 21 PEKANBARU - Eni Susanti; Otang Kurniaman; Lazim. N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve the skills of reading comprehension discourse at students of Class IV SD Negeri 21 Pekanbaru by applying preview Question Read Reflect Strategy Review Recite (PQ4R). The subjects in this study is the fourth grade students of SD Negeri 21 Pekanbaru, the number of students 25 people consisting of 10 student-sex male and 15 female students. From the results of this study concluded that application of Reflect Strategy preview Question Read Recite Review (PQ4R) can improve reading comprehension skills discourse at fourth grade students of SDN 21 Pekanbaru. Is detailed as follows: (1) Increased activity of teachers and students at each meeting. At the first meeting the activity of only 54.17% of teachers with enough categories, then increased in the second meeting as much as 8.33% to 62.50% with the good category. At the third meeting increased again as much as 12.50% to 75% with the good category and at the fourth meeting increase again as much as 20.83% to 95.83% with very good category. While the activities of students at the first meeting only 45.83% with less category, then increased in the second meeting as much as 12.50% to 58.33% with the category enough. At the third meeting increased again as much as 12.50% to 70.83% with the good category and at the fourth meeting also increased by 16.67% to 87.50% with very good category. (2) Improved student learning completeness individually and classical. At the base score of students who completed only 11 people with a percentage of 44%, in the first cycle increased to 16 people with a percentage of 64%, an increase of 5 or 20%, and the second cycle increased to 22 students with a percentage of 88%, occurred an increase of 6 students, or 24%. In addition, the average value of reading comprehension skills discourse at fourth grade students of SDN 21 Pekanbaru also increased in each cycle. At the base score is the average value obtained only 57 students,then the first cycle increased by 10.88% to 63.20 and the second cycle increased by 26.32% to 72Keywords: Strategies Reflect Preview Question Read Recite Review (PQ4R),Reading ComprehensionSkillsDiscourse